Reductive Cyclizations of Nitroarenes to Hydroxamic Acids by Visible Light Photoredox Catalysis - Cismesia, Megan A.; Ischay, Michael A.; Yoon, Tehshik P. (Synthesis, 2013)
We have developed a photocatalytic reduction of nitroarenes as an efficient, chemoselective route to biologically important N-phenyl hydroxamic acid scaffolds. Optimal conditions call for 2.5 mol% of a ruthenium photocatalyst, visible light irradiation, and a dihydropyridine terminal reductant. Because of the mild nature of the visible light activation, functional groups that might be sensitive to other non-photochemical reduction methods are easily tolerated.
Keywords: electron transfer; heterocycles; hydroxamic acids; photochemistry; reduction